(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The main goal of this paper is to create a valid and reliable model showing the combined effect of various factors (external factors and demographic characteristics) on inclination towards impulse buying by consumers in Bosnia and Herzegovina. Buying behavior of consumer is always unique, personal and emotional nature. Buying motive of each and every consumer is different and her buying behavior is driven by personal and social characteristics. Consumer behavior is determined by a number of factors and is therefore characterized as very complex and difficult to predict, and studying of impulse behavior is therefore a special challenge for marketing studies and practice. This paper will study whether external factors (advertising approach, presentation of products, surroundings in the shop, discounts, credit card use for purchasing) and demographic characteristics of buyers (gender, age, level of education, number of family members and income) affect the inclination towards impulse buying among consumers in Bosnia and Herzegovina. Based on the study, it has been concluded that there is a small influence of external factors on tendency for impulse buying by consumers in Bosnia and Herzegovina (discount and the use of credit cards do not affect the consumer’s impulsiveness), while, out of all demographic characteristics, gender and number of family members have the most impact on impulse purchase.